Les médias et l'opinion- Eléments théoriques et méthodologiques pour une analyse du débat sur l'identité nationale. Issue 1 (January 2013) - Marty, Emmanuel; Marchand, Pascal; Ratinaud, Pierre
The Media and Public Opinion - Theoretical and Methodological Analysis of the Debate on National Identity : This article deals with the "great debate on national identity" initiated by the Ministry of Immigration, Integration, National Identity and Mutually-Supportive Development in the winter of 2009-2010. Using the theory of framing (Bateson, 1972; Entman, 1993;Chong and Druckman, 2007 ), it seeks to identify the relationship between permeability and public debate as it is shown on the Web and the media coverage of the latter. To do this, a crossed lexicometric analysis of two corpora was done: on one hand, the 18, 240 contributions posted on the dedicated ministerial site; on the other, the 1, 436 press articles published from 25 October to 2 December 2009. A descending hierarchical classification was done with the Iramuteq software and identified, by their lexicon, places of permeability between personal and media frameworks in the apprehension of the debate, but also the specific universes of discourse to one or other corpora. We present them here in a detailed manner while proposing explanatory approaches of their dynamics.